The Importance of Local Wisdom in Higher Education as a Philosophy of Strengthening the Character of State Defense - Sudaryatie Sudaryatie; Wahyu Wibowo Eko Yulianto; Hani Subagio; Danang Prasetyo (Ideas Publishing, 2022)
This paper seeks to describe the existence of local wisdom values that can be used as teaching materials to strengthen the character of defending the state through state defence courses in universities, as well as to attempt to provide an understanding that protecting the country is a necessity for peoples lives as individuals and citizens of a country so that state defence implementation is based on awareness and sincerity, rather than coercion or doctrine. This study is the outcome of descriptive qualitative research using primary data sources from interviews with numerous course professors and students. Secondary data sources include papers, manuscripts of scientific journal articles, internet media stories, and relevant literature on the Philosophy of Strengthening. The findings of this study point to the incorporation of local wisdom values that exist among the people of Yogyakarta as the key material for state defence training. These ideals are frequently heard by the general public as life slogans, such as (1) gandeng gendong; (2) ngluruk tanpa bala, menang tanpa ngasorake, sekti tanpa aji-aji, sugih tanpa bandha; dan (3) durung menang yen durung wani kalah, durung unggul yen durung wani asor, durung gedhe yen durung wani cilik. These character values ​​will be understood collectively and practised in daily life in the context of student participation in non-physical efforts to defend the country. Tulisan ini bertujuan memaparkan keberadaan nilai kearifan lokal yang dapat dijadikan materi ajar penguatan karakter bela negara melalui mata kuliah bela negara di perguruan tinggi. Tulisan ini merupakan hasil penelitian kualitatif deskriptif dengan sumber data primer berasal dari wawancara terhadap dosen pengampu mata kuliah, mahasiswa. Selanjutnya data sekunder berasal dari dokumen-dokumen, naskah publikasi jurnal ilmiah, berita media online, dan literatur yang relevan. Adapun hasil penelitian ini menunjukkan bahwa pengintegrasian nilai kearifan lokal yang hidup di masyarakat Yogyakarta untuk dijadikan materi ajar mata kuliah bela negara. Adapun nilai-nilai tersebut sering didengar masyarakat luas sebagai slogan hidup, seperti (1) gandeng gendong; (2) ngluruk tanpa bala, menang tanpa ngasorake, sekti tanpa aji-aji, sugih tanpa bandha; dan (3) durung menang yen durung wani kalah, durung unggul yen durung wani asor, durung gedhe yen durung wani cilik. Nilai karakter tersebut akan dipahami bersama, dan diamalkan dalam kehidupan seharai-hari dalam rangka peran serta mahasiswa dalam upaya bela negara secara non-fisik.